Deep Extension from Carcinoma Arising from the Gingiva: CT and MR Imaging Features - Kimura, Yasuo; Sumi, Misa; Sumi, Tadateru; Ariji, Yoshiko; Ariji, Eiichiro; Nakamura, Takashi (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: CT and MR imaging are useful for evaluating the extension of carcinomas in the face and neck. We evaluated the involvement by carcinoma arising from the gingiva (ie, gingival cancer) by using CT and MR imaging.METHODS: We retrospectively examined 122 patients with squamous cell carcinoma (SCCA) in the lower (88 patients) and upper (34 patients) gingiva. Extension of SCCA into the spaces of the face and neck was evaluated with CT and MR imaging, and findings were surgically confirmed.RESULTS: Spread into the face and neck spaces occurred in 58% of patients. The buccal space was the most common site of spread, occurring in 42% of the lower and of 47% of the upper gingival cancers. Spread into the masticator space occurred from the lower gingival cancers in the molar region (20%) but not from the anterior region. Masticator space involvement from the upper gingiva was rare (4%). The retromolar triangle and buccal space immediately anterior to the ramus served as a corridor for cancer extension from the lower gingiva into the masticator space. The sublingual space (11%) was a less common site of spread from the lower gingiva.CONCLUSION: Gingival cancers spread into the masticator, buccal, and sublingual spaces depending on the primary sites in the oral cavity. An understanding of the face and neck-space anatomy is important in diagnosing cancer extension in the oral cavity gingiva and in treating patients with such disease.